PENGARUH PAPARAN PERASAN WORTEL TERHADAP KADAR ASAM URAT PADA LANSIA - Lina Safarina; Perdina Nursidika (Poltekkes Kemenkes Bandung, 2021)
Uric acid is the final product of purine nucleic acids. Uric acid is filtered by the glomerulus and secreted through the distal tubule to the urine, most uric acid is reabsorbed in the proximal tubule and utilized. Uric acid is not soluble in plasma and at high concentrations will be stored in joints and tissues, it causing painful inflammation. One that can reduce hyperuricemia is carrots. Urination through food, one of the carrots can accelerate uric acid through urine. Carrots contain high antioxidants such as carotenoids such as β-carotene. Carrots have diuretic properties, N balance agents, and are effective for removing gout. Vitamin A in carrots is proven to reduce uric acid levels because vitamin A in carrots will be converted to retinoic acid and xanthin by xanthine oxidase there will be no uric acid formation. This study aims to determine the impact of carrot extract on uric acid levels in the elderly in the working area of ​​Cimahi City Cipageran Health Center which was intervened for 30 days. The method used were quasi experimental pre post one design group. Data collection was done by measuring the uric acid level of the elderly, then intervening in giving carrot water to the elderly with gout in the working area of ​​Cipageran Health Center and measuring uric acid levels after intervention. Analysis of univariate data with mean and bivariate tests with t test. The average result of uric acid before being given carrot extract was 7.6 mg / dL with a standard deviation of 0.417 mg / dL and an error standard of 0.07 mg / dL, while the average uric acid level after being given carrot juice was 6.7 mg / dL with a standard deviation of 0.967 mg / dL and a standard error of 0.182 mg / dL. The statistical test results obtained pValue = 0.001. From the results of the study it can be concluded that uric acid levels can be lowered due to the intervention of carrot extract.